The feasibility of classical biological control of two major cowpea insect pests - Tamo, Manuele; Bottenberg, H.; Arodokoun, D.; Adeoti, R. (1997)
Biological control, as a key component of biointensive IPM in cowpea, is evaluated for its practical feasibility. The case study of one of the major insect pests, the bean flower thrips Megalumthrips sjosredti (Trybom) (Thysanoptera, Thripidae), is used to indicate the most important criteria for this evaluation: the nature of the pest and the release habitat, the availability and effectiveness of biological control agents, and the current status of biocontrol against the target pest. Although laxonomic aspects need further consideration, present knowledge suggests a southeast Asian origin for M. sjostedlt. In the savannas of West Africa, cultivated and wild host plants are always available to sustain the feeding and reproduction of the pest throughout the year, while the locally present natural enemies are unable to control its population. A first exploration in search of M. sjostedti and efficient natural enemies, undertaken in Malaysia in November-December 1994, yielded an endophagous larval parasitoid, tentatively identified as Ceranisus menes Walker (Hymenoptera, Eulophidae). This parasitoid was able to parasitize up to 70% of the larvae of the closely related species, M. usilalus, found in flowers of Pueraria phaseoloides, a commonly grown cover crop. In a second, less detailed case study, the biocontrol feasibility for another key pest, the legume pod borer, Marnca vitrata Fabricius (previously M. testuUilis Geyer) (Lepidoptera, Pyralidae). is assessed, using the same criteria. These feasibility studies indicate that (1) both pests might be of foreign origin: (2) the alternative host plant habitat is conducive to the perennial presence of the pests; (3) the indigenous antagonists are not effective in controlling the pests; and (4) potential natural enemies of both pests have been identified in southeast Asia. Additional foreign explorations are needed to substantiate the results of these studies.